Low Education and Early Marriage in Madura: a Literature Review - Bawono, Yudho; Suminar, Dewi Retno; Hendriani, Wiwin (The Journal of Educational Development, 2019)
A number of data show that early marriages still occur in Madura. This is caused by several factors, one of which is low education. This study took place in Madura because in Madura early marriage is still quite a lot done. Some of the underlying factors are the Islamic understanding that if a child is already adult (baligh), they can already get married. In addition, Madurese people still adhere to the tradition of matchmaking and the existence of a belief called sangkal (if women reject applications from men, they will become spinsters or ta paju lake '). This study aims to conduct a literature review on the low level of education with the occurrence of early marriage in Madura. Literature search is done through portalgaruda.org, google scholar, and onesearch.id database by using the keywords "pernikahan diniâ€ (â€œearly marriageâ€) and â€œtingkat pendidikanâ€ (â€œlevel of educationâ€). The literature collected by using these keywords are 31 articles, but after adding the keyword "Madura" the literature collected becomes 7 articles. The method used in this study is a study of narrative literature. The study shows that low education plays a role in the occurrence of early marriage in Madura.